Different genotypes of Brugada syndrome may present different clinical phenotypes: electrophysiology from bench to bedside - El-Battrawy, Ibrahim; Lang, Siegfried; Zhou, Xiao-Bo; Akın, Ibrahim (European heart journal, 2021)
This commentary refers to ‘Brugada syndrome genetics is associated with phenotype severity’ by G. Ciconte et al., doi: 10.1093/eurheartj/ehaa942 and the discussion piece ‘Common modulators of Brugada syndrome phenotype do not affect SCN5A prognostic value’ by C. Pappone et al., doi:10.1093/eurheartj/ehab071.The article by Ciconte et al.1 published in the European Heart Journal describing the relevance of genetic background on the clinical phenotype of Brugada syndrome (BrS) elucidated great interest among researcher of our working group. Authors showed that electrophysiological abnormalities in BrS are determined by the genetic background. Carriers of SCN5A mutations exhibited more pronounced epicardial abnormalities and more aggressive clinical presentation.
Gesehen am 13.07.2021